Abnormal auditory mismatch fields in adults with autism spectrum disorder. (17th April 2019) - Matsuzaki, Junko; Ku, Matthew; Berman, Jeffrey I.; Blaskey, Lisa; Bloy, Luke; Chen, Yu-han; Dell, John; Edgar, J. Christopher; Kuschner, Emily S.; Liu, Song; Saby, Joni; Brodkin, Edward S.; et al.
Highlights: Delayed vowel discrimination process in adults with autism spectrum disorder. Abnormal rightward lateralization in adults with autism spectrum disorder. Delayed MMF response was decoupled from the earlier auditory M100 response delay. Abstract: The auditory mismatch field (MMF) is a pre-attentive processing component, reflecting neural discrimination and inhibitory processing. Abnormal MMFs have been reported in children with autism spectrum disorder (ASD) along with an association with abnormal language comprehension; however, relatively little is known about MMF abnormalities to contrasting vowel stimuli in adults with ASD. To better understand the neurophysiological mechanisms underlying auditory language discrimination of vowel stimuli in individuals with ASD, magnetoencephalography was used to measure MMFs during an auditory oddball paradigm with vowel stimuli (/a/ and /u/) in adults with ASD. MMFs arising from left and right superior temporal gyrus are reported from nine high-functioning right handed males with ASD (22.22 ± 5.74yrs) and sixteen typically developing (TD) right handed males (27.25 ± 6.63yrs). The MMF was delayed in adults with ASD (188.90 ± 5.8 ms) as compared to the TD participants (173.08 ± 4.31 ms, p < 0.05). Replicating previous findings in children, the earlier M100 component to single stimulus tokens was also delayed in adults with ASD (108.59 ± 4.1 ms) compared to the TD participants (94.60 ± 3.0 ms, p < 0.05). However, there was no correlation between delayed M100 latency and MMF latency. Furthermore, whereas TD participants showed a leftward lateralization of MMF amplitude, participants with ASD showed an opposite (rightward) lateralization. Findings suggest that adults with ASD have hemispherically- and temporally- abnormal auditory discrimination processing in addition to and distinct from abnormal neurophysiological mechanisms in earlier cortical responses.